IL-17A-producing CD8+ T cells promote PDAC via induction of inflammatory cancer-associated fibroblasts - Picard, Felix Simon Ruben; Lutz, Veronika; Brichkina, Anna; Neuhaus, Felix; Ruckenbrod, Teresa; Hupfer, Anna; Raifer, Hartmann; Klein, Matthias; Bopp, Tobias; Pfefferle, Petra Ina; Savai, Rajkumar; Prinz, Immo; et al. (Gut, 2023)
Objective Pancreatic ductal adenocarcinoma (PDAC) is characterised by an abundant desmoplastic stroma composed of cancer-associated fibroblasts (CAF) and interspersed immune cells. A non-canonical CD8+ T-cell subpopulation producing IL-17A (Tc17) promotes autoimmunity and has been identified in tumours. Here, we evaluated the Tc17 role in PDAC. - Design Infiltration of Tc17 cells in PDAC tissue was correlated with patient overall survival and tumour stage. Wild-type (WT) or Il17ra-/- quiescent pancreatic stellate cells (qPSC) were exposed to conditional media obtained from Tc17 cells (Tc17-CM); moreover, co-culture of Tc17-CM-induced inflammatory (i)CAF (Tc17-iCAF) with tumour cells was performed. IL-17A/F-, IL-17RA-, RAG1-deficient and Foxn1nu/nu mice were used to study the Tc17 role in subcutaneous and orthotopic PDAC mouse models. - Results Increased abundance of Tc17 cells highly correlated with reduced survival and advanced tumour stage in PDAC. Tc17-CM induced iCAF differentiation as assessed by the expression of iCAF-associated genes via synergism of IL-17A and TNF. Accordingly, IL-17RA controlled the responsiveness of qPSC to Tc17-CM. Pancreatic tumour cells co-cultured with Tc17-iCAF displayed enhanced proliferation and increased expression of genes implicated in proliferation, metabolism and protection from apoptosis. Tc17-iCAF accelerated growth of mouse and human tumours in Rag1-/- and Foxn1nu/nu mice, respectively. Finally, Il17ra-expressed by fibroblasts was required for Tc17-driven tumour growth in vivo. - Conclusions We identified Tc17 as a novel protumourigenic CD8+ T-cell subtype in PDAC, which accelerated tumour growth via IL-17RA-dependent stroma modification. We described a crosstalk between three cell types, Tc17, fibroblasts and tumour cells, promoting PDAC progression, which resulted in poor prognosis for patients.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 03.05.2023